Legality, Proportionality and Protection in Public Order Enforcement by Satpol PP in Batam, Indonesia - Irwan, Irwan; Maileni, Dwi Afni; Bhakti, Rizki Tri Anugrah; Kelvin, Edwar (Ranah Research : Journal of Multidisciplinary Research and Development, 2026)
This study examines the interplay of legality, proportionality and rights protection in enforcement operations conducted by the Satpol PP in Batam, Indonesia. Local-order enforcement against violations of regional regulations often triggers contestation because it intersects with livelihoods, property interests and security while simultaneously demanding effective public-order governance. The research aims to assess whether enforcement actions comply with applicable mandates and procedural requirements; evaluate how proportionality is applied in selecting measures, escalating interventions and using force; and map available safeguards and remedies for affected residents. A socio-legal case-study design is employed, combining document analysis, field observation and semi-structured interviews with Satpol PP officers, local government units, street vendors and business actors and civil-society representatives. Findings suggest legality is generally satisfied at the level of formal authority, yet procedural weaknesses persist in advance notice, record-keeping, transparency of decision-making and post-operation accountability. Proportionality is not consistently operationalized, particularly regarding the least restrictive option, clear escalation stages and standards on the use of force. Rights protection for impacted communities remains dependent on discretion, with complaint channels and restitution mechanisms insufficiently accessible, especially for vulnerable groups. The study recommends strengthening rights-based SOPs, institutionalizing proportionality training, improving documentation and supervisory controls and providing accessible complaint, mediation and relocation-support pathways. More broadly, inter-agency coordination and performance metrics should prioritize voluntary compliance and reduced grievances, not merely the number of operations, to enhance legitimacy and protect citizens in governance.